Desenvolvimento Humano Relatório de 2023/2024 - United Nations Development Programme (United Nations, 2024)
Today, collective action on challenges ranging from climate change mitigation to peace and security is frustratingly slow or stymied altogether. Lack of trust and polarization–both associated with insecurity–exacerbate the gridlock. Shared, interlinked global challenges, like the pandemic and its recovery, are outpacing our willingness and our institutions’ capacities to respond to them. Why, despite all our riches and technologies, are we so stuck? How do we get unstuck? Is it possible to mobilize action to address globally shared challenges in a world that is intensively polarized? The 2023-2024 Human Development Report explores these issues and offers a platform for strategic discussion on how to move beyond narrow zero-sum thinking and support cooperation even as we have diverging interests and views.